Statistical Analysis of a Clinical Trial in Orthostatic Hypotension -a Nonparametric Approach - Haux, R.; Immich, H.; Schumacher, M. (Methods of Information in Medicine, 1987)
Some basic problems and considerations of analyzing clinical trials, in which a large amount of data is recorded on very few patients - mostly in the form of serial measurements -, are highlighted within the framework of a clinical trial in orthostatic hypotension. The method suggested to analyze these kinds of trials renounces the use of complex mathematical models and complicated statistical methods. It is simply based on the derivation of relevant aspects of the patient’s profiles and the use of well-known nonparametric tests and requires only a very simple study design. With this procedure, however, it is possible to satisfy at least the basic requirements of clinical trial methodology.
Keywords: Orthostatic Hypotension; Clinical Trial; Nonparametric Approach